2022
DOI: 10.1002/ctm2.982
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MEN1 leads to renal fibrosis and decreases HGF‐Adamts5 pathway activity via an epigenetic mechanism

Abstract: Background Renal fibrosis is a serious condition that results in the development of chronic kidney diseases. The MEN1 gene is an epigenetic regulator that encodes the menin protein and its role in kidney tissue remains unclear. Methods Kidney histology was examined on paraffin sections stained with hematoxylin‐eosin staining. Masson’s trichrome staining and Sirius red staining were used to analyze renal fibrosis. Gene and protein expression were determined by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Here we show that, in addition to having this quantitative effect, MEN1 also impacts the quality of transcripts by altering exon skipping in the pre-mRNAs of some genes. We and others have previously demonstrated that MEN1 inactivation or deletion leads to various human diseases, such as renal fibrosis ( 67 ), diabetes ( 68 ) and lung cancers ( 21 ). Since the AS program tightly controls the quantity and quality of post-transcriptional gene expression, which plays a crucial role in diverse cellular processes, including cell proliferation, differentiation and death, we therefore reason that these defects are caused in part by abnormal AS programs upon MEN1 dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that, in addition to having this quantitative effect, MEN1 also impacts the quality of transcripts by altering exon skipping in the pre-mRNAs of some genes. We and others have previously demonstrated that MEN1 inactivation or deletion leads to various human diseases, such as renal fibrosis ( 67 ), diabetes ( 68 ) and lung cancers ( 21 ). Since the AS program tightly controls the quantity and quality of post-transcriptional gene expression, which plays a crucial role in diverse cellular processes, including cell proliferation, differentiation and death, we therefore reason that these defects are caused in part by abnormal AS programs upon MEN1 dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This process is accompanied by inflammatory cell infiltration, the release of inflammatory mediators, and the activation of fibroblasts in the renal interstitium. These events culminate in renal interstitial fibrosis, causing the destruction of kidney structure and impairing its overall function [ [4] , [5] , [6] ]. The most significant pathological feature of obstructive nephropathy is renal interstitial fibrosis, the degree of which has close relation to the patient’s prognosis.…”
Section: Introductionmentioning
confidence: 99%